Leitura-escrita colaborativa mediada por tecnologias educacionais em rede no ensino médio politécnico - Marques, Eliandra Gomes (2015)
We investigated the possibilities and limits of collaborative reading-writing mediated by Virtual Learning Environment (VLE) at the medium level polytechnic schools. In this sense, we developed a action-research with teachers of the Federal University of Santa Maria (UFSM), a coordinator of Portuguese idiom teaching, and students of the second and third years of a medium level polytechnic state school in São Francisco de Assis (RS). The study was driven during the second semester of 2014 and first semester of 2015. We adopted the methodological conception of action-research because our intention do not limit itself to discover or describe a pedagogical practice, but mostly to transform it through action-reflection-action cycles. We proposed collaborative reading-writing practices mediated by a Moodle wiki system, in the context of medium level teaching. These practices evidence the dialogical problem posing notion, and thus, they showed up as an innovative alternative to the teaching-learning process. Finally, we highlighted limits and possibilities which emerged from the concrete action, evidencing that the collaboration and the dialogical problem poser are essential for the reading-writing practice in Portuguese idiom. We also pointed that, beyond driving a digital literacy with the students, the pedagogical practices mediated by networked technologies enhanced new knowledge acquisition and production modes.